Experimental investigation of effect of flow attack angle on thermohydraulic performance of air flow in a rectangular channel with discrete V-pattern baffle on the heated plate. (May 2016) - Kumar, Raj; Chauhan, Ranchan; Sethi, Muneesh; Sharma, Ashutosh; Kumar, Anil
In this work, the effect of angle of attack( α a ) of the discrete V-pattern baffle on thermohydraulic performance of rectangular channel has been studied experimentally. The baffle wall was constantly heated and the other three walls of the channel were kept insulated. The experimentations were conducted to collect the data on Nusselt number( N u b ) and friction factor( f b ) by varying the Reynolds number ( Re ) = 3000–21, 000 and angle of attack( α a ) from 30° to 70°, for the kept values of relative baffle height( H b / H ) = 0 . 50, relative pitch ratio( P b / H ) = 1 . 0, relative discrete width( g w / H b ) = 1 . 5 and relative discrete distance( D d / L v ) = 0 . 67 . As compared to the smooth wall, the V-pattern baffle roughened channel enhances the Nusselt number( N u b ) and friction factor( f b ) by 4.2 and 5.9 times, respectively. The present discrete V-pattern baffle shapes with angle of attack( α a ) of 60° equivalent to flow Reynolds number of 3000 yields the greatest thermohydraulic performance. Discrete V-pattern baffle has improved thermal performance as compared to other baffle shapes' rectangular channel.